2019
DOI: 10.7554/elife.49826
|View full text |Cite
|
Sign up to set email alerts
|

A novel lineage of candidate pheromone receptors for sex communication in moths

Abstract: Sex pheromone receptors (PRs) are key players in chemical communication between mating partners in insects. In the highly diversified insect order Lepidoptera, male PRs tuned to female-emitted type I pheromones (which make up the vast majority of pheromones identified) form a dedicated subfamily of odorant receptors (ORs). Here, using a combination of heterologous expression and in vivo genome editing methods, we bring functional evidence that at least one moth PR does not belong to this subfamily but to a dis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 55 publications
4
56
0
Order By: Relevance
“…However, according to the FPKM values, HrhoOR14 exhibited male-biased expression while HrhoOR30 exhibited female-biased expression. This expression pattern was similar to the novel lineage of PRs, whereby approximately one-half of the ORs were male-biased and the other half were female-biased (Bastin-Héline et al, 2019).…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…However, according to the FPKM values, HrhoOR14 exhibited male-biased expression while HrhoOR30 exhibited female-biased expression. This expression pattern was similar to the novel lineage of PRs, whereby approximately one-half of the ORs were male-biased and the other half were female-biased (Bastin-Héline et al, 2019).…”
Section: Discussionsupporting
confidence: 62%
“…However, two ORs (HrhoOR14 and 30) clustered into a novel lineage distantly related to the conserved lepidopteran PR clade. Notably, several DpunPRs (Shen et al, 2020) and SlitOR5 (Bastin-Héline et al, 2019) that grouped with HrhoOR14 and 30 were recently characterized as a new evolution origin of PRs in Lepidoptera. We speculate that these two ORs may be involved in the detection of H. rhodope sex pheromones, although further functional analysis is needed to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we noticed that the two other minor pheromone components (Z11-16:OAc and Z7-12:OAc) failed to activate any of the six ORs tested, suggesting that some other ORs outside the PR clade are responsible for their detection. Recently, it was reported that in S. littoralis, SlittOR5, a member of the general odorant receptor clade, responds to the sex pheromone component Z9,E11-14:OAc, rather than one of the receptors in the PR clade [62].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, H. rhodope ORs lacked in the classical moth pheromone receptor (PR) clade, while HrhhoOR14 and HrhoOR30 clustered within a novel PR clade containing SlitOR5 in S. littoralis and several candidate PRs from D. punctatus. These ORs were recently identified as a novel lineage of PRs detecting type Ⅰ pheromones in Lepidoptera(Bastin-Héline et al, 2019;Shen et al, 2020).…”
mentioning
confidence: 99%